Turkey : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This report for the 2012 Article IV Consultation with Turkey discusses the macroeconomic conditions after the 2008 global financial crisis. After two years of rapid growth, the economy has slowed and imbalances are unwinding. However, owing to slower domestic demand, the Turkish financial system continues to remain sound. IMF staff supports the authorities' fiscal objective for 2013 and also the medium-term fiscal plan for 2013-15. But, they recommend a tighter monetary policy stance given the upside risks to inflation.